2017
DOI: 10.1007/s10067-017-3597-6
|View full text |Cite
|
Sign up to set email alerts
|

CD16-positive circulating monocytes and fibrotic manifestations of systemic sclerosis

Abstract: The objective of this study is to assess the association of clinical manifestations of systemic sclerosis (SSc) with the absolute count of circulating blood monocyte subpopulations according to their membrane expression of CD16. Forty-eight consecutive patients fulfilling the 2013 ACR/EULAR classification criteria for SSc were included in this cross-sectional study. CD16+ monocyte absolute count was defined by flow cytometry and confronted to the clinical characteristics of SSc patients. Twenty-three healthy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 20 publications
4
37
1
Order By: Relevance
“…Similarly, the PI of MDM was significantly decreased in M1 HD MDM in comparison with M0 and M2a (Figure b), confirming some previous data . This downexpression of ITGβ5 both in M1 HD MDM and in SSc support the recent results from our group and others, suggesting that blood monocytes and MDM from patients with SSc not only display profibrotic properties but also share some characteristics with proinflammatory M1 MΦ …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the PI of MDM was significantly decreased in M1 HD MDM in comparison with M0 and M2a (Figure b), confirming some previous data . This downexpression of ITGβ5 both in M1 HD MDM and in SSc support the recent results from our group and others, suggesting that blood monocytes and MDM from patients with SSc not only display profibrotic properties but also share some characteristics with proinflammatory M1 MΦ …”
Section: Resultssupporting
confidence: 91%
“…12 This downexpression of ITGb5 both in M1 HD MDM and in SSc support the recent results from our group and others, suggesting that blood monocytes and MDM from patients with SSc not only display profibrotic properties but also share some characteristics with proinflammatory M1 MΦ. 13,22,25 From a pathogenic viewpoint, the decreased efferocytosis capacities of MΦ may play a key role in the autoimmune processes associated with SSc and connective tissue diseases in general. Impaired efferocytosis is indeed a shared characteristic between SLE, Sj€ ogren syndrome 6,7 and, as suggested by our work, SSc.…”
Section: Comparison Of Efferocytosis Capacities Of Monocytederived Mamentioning
confidence: 99%
“…Additionally, the patients in this cluster had the strongest increase of circulating CXCL10 and CXCL11, chemokines previously associated with SSc disease progression and severity . These observations corroborate previous findings of increased numbers of monocytes in circulation and skin of SSc patients and an increase of CD16 + non‐classical monocytes observed in diffuse SSc patients . Further supporting the fact that monocytes might be central mediators in the pathophysiology of SSc, it was recently shown that the interferon signature is present in SSc monocytes even before the onset of overt fibrosis .…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, blood MDMs’ polarisation states contrast with the macrophage signature from other tissues in SSc,3 such as lung, in which a STAT3-dependent enhanced expression of CD163 has been associated with an immune-driven pulmonary fibrosis. The results of Moreno-Moral et al on MDMs are consistent with the results of previous studies on undifferentiated peripheral blood monocytes in SSc4 in which the inflammatory component of the immune-fibrotic processes is only found in peripheral blood, illustrating this mixed (M1/M2) polarisation signature of blood monocytes and MDMs 1 3. Altogether, these results reinforce the vision of a wide and heterogeneous functional range of activated macrophages, not only depending on the disease at stake and its stage of evolution, but also on the organ of interest, highlighting the need for a more refined phenotypic characterisation of these so-called ‘M1 and M2’ macrophages in inflammatory and fibrotic disorders.…”
supporting
confidence: 90%